PENGARUH KEPUASAN HARGA TERHADAP NIAT PEMBELIAN ULANG DENGAN VARIABEL CUSTOMER PERCEIVED VALUE SEBAGAI PEMEDIASI PADA PENGGUNA KARTU INTERNET TELKOMSEL DI BANDA ACEH - Runaika, Nafisya; Nizam, Ahmad (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to measure the role of price satisfaction and customer perceived value for repurchase intention of Kartu Internet Telkomsel users in Banda Aceh. The sample used in this study were Telkomsel internet card?s user with total of 185 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is purposive sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all the variables involved. Based on the results of the HLM analysis indicated that price satisfaction positively influence repurchase intention, price satisfaction positively influence customer perceived value, customer perceived value positively influence repurchase intention, customer perceived value mediates partially the relationship between price satisfaction and repurchase intention. Keywords: Price Satisfaction, Repurchase Intention, Customer Perceived Value, Hierarchical Linear Modelling